MELALUI PKM UNIVERSITAS PAMULANG : MARI KITA TINGKATKAN JEJARING PEMASARAN POSYANTEK DALAM MENYONGSONG ERA INDUSTRI 4.0 - Putranto, Agung Tri; Widodo, Arif Siaha; Hanny, Risa; Septiani, Fauziah; Armansyah, Armansyah (LPPM Universitas Pamulang, 2020)
This service is titled Through Community Service at Pamulang University. Let's Improve Posyantek Marketing Network in Welcoming the Industrial Era 4.0. The purpose of community service is to provide knowledge about TTG (Appropriate Technology) as a solution in improving the business of UKM members of Posyantek. The method of implementing this service is carried out in a number of activities, namely by involving many parties other than the Appropriate Technology Service Post (Posyantek) also involving parties from the sub-district starting from the Camat, and the subdistrict staff in the Setu sub-district of South Tangerang City, Banten Province. The conclusion of community service (PKM) is that in general community service activities can be carried out well and have been welcomed and supported by the District of Setu in terms of place, infrastructure and accommodation, as well as enthusiastic participants, namely the Posyantek management and UKM Posyantek members in Setu District, so as to create awareness of the importance of improving marketing networks in the industrial era 4.0.